Feasibility of robot‐assisted prostatectomy performed at ultra‐low pneumoperitoneum pressure of 6 mmHg and comparison of clinical outcomes vs standard pressure of 15 mmHg. (7th February 2019) - Ferroni, Matthew C.; Abaza, Ronney
Abstract : Objectives: To evaluate the feasibility of performing robot‐assisted laparoscopic prostatectomy (RALP) at an ultra‐low pressure of 6 mmHg and to assess the potential impact on its clinical outcomes, as compared to those of a historical cohort of patients in which RALP was performed at a pressure of 15 mmHg. Patients and Methods: We evaluated 600 consecutive RALP procedures, performed by a single surgeon, including 300 procedures performed at 6 mmHg and the previous 300 performed at 15 mmHg. We compared preoperative patient characteristics and outcomes including pain scores, morphine equivalents, length of stay (LOS) and complications. After implementing the adjustment to 6 mmHg, we began allowing same‐day discharge in patients meeting established criteria. Results: All 300 consecutive RALP procedures were completed at 6 mmHg with no pressure adjustments for the entirety of the case. There were no significant differences in patient or pathological features between groups. Body mass index was 19.5–44.3 kg/m 2 in the 6 mmHg group. The mean operating time was 10.5‐min longer and mean estimated blood loss 20‐mL higher at 6 mmHg, with no blood transfusions in either group. The mean LOS was shorter in the 6‐mmHg group (0.57 vs 1.00 days; P < 0.001), with 43.3% of patients in the 6‐mmHg group discharged home the day of surgery. There were no differences in morphine equivalents or maximum pain scores in the first 4 h after surgery, but there was a small improvement (18%) in pain scores at 5–12 h postoperatively (3.2 vs 3.9; P < 0.001). The 30‐day complication rate was 8.7% vs 4.0%, with 30‐day hospital readmissions of 5.7% vs 1.0% for the 15 vs 6 mmHg groups. Conclusion: Robot‐assisted laparoscopic prostatectomy at a pneumoperitoneum pressure of 6 mmHg was uniformly feasible without increasing complications. Ultra‐low pneumoperitoneum may confer a pain benefit, which may contribute to safe same‐day discharge.